Kinesin-13 and Kinesin-8 Function during Cell Growth and Division in the Moss Physcomitrella patens - Leong, Shu Yao (Plant Cell, 2020)
Kinesin-13 and Kinesin-8 are well-known microtubule (MT) depolymerases that regulate MT length and chromosome movement in animal mitosis. While much is unknown about plant Kinesin-8, Arabidopsis (Arabidopsis thaliana) and rice (Oryza sativa) Kinesin-13 have been shown to depolymerize MTs in vitro. However, the mitotic function of both kinesins has yet to be determined in plants. Here, we generated complete null mutants of Kinesin-13 and Kinesin-8 in moss (Physcomitrella patens). Both kinesins were found to be nonessential for viability, but the Kinesin-13 knockout (KO) line had increased mitotic duration and reduced spindle length, whereas the Kinesin-8 KO line did not display obvious mitotic defects. Surprisingly, spindle MT poleward flux, which is mediated by Kinesin-13 in animals, was retained in the absence of Kinesin-13. MT depolymerase activity was not detectable for either kinesin in vitro, while MT catastrophe-inducing activity (Kinesin-13) or MT gliding activity (Kinesin-8) was observed. Interestingly, both KO lines showed waviness in their protonema filaments, which correlated with positional instability of the MT foci in their tip cells. Taken together, the results suggest that plant Kinesin-13 and Kinesin-8 have diverged in both mitotic function and molecular activity, acquiring roles in regulating MT foci positioning for directed tip growth.